Atomic layer deposition assisted fabrication of large-scale metal nanogaps for surface enhanced Raman scattering. (25th June 2023) - Cheng, Tangjie; Zhu, Zebin; Wang, Xinxin; Zhu, Lin; Li, Aidong; Jiang, Liyong; Cao, Yanqiang
Abstract: Metal nanogaps can confine electromagnetic field into extremely small volumes, exhibiting strong surface plasmon resonance effect. Therefore, metal nanogaps show great prospects in enhancing light–matter interaction. However, it is still challenging to fabricate large-scale (centimeter scale) nanogaps with precise control of gap size at nanoscale, limiting the practical applications of metal nanogaps. In this work, we proposed a facile and economic strategy to fabricate large-scale sub-10 nm Ag nanogaps by the combination of atomic layer deposition (ALD) and mechanical rolling. The plasmonic nanogaps can be formed in the compacted Ag film by the sacrificial Al2 O3 deposited via ALD. The size of nanogaps are determined by the twice thickness of Al2 O3 with nanometric control. Raman results show that SERS activity depends closely on the nanogap size, and 4 nm Ag nanogaps exhibit the best SERS activity. By combining with other porous metal substrates, various sub-10 nm metal nanogaps can be fabricated over large scale. Therefore, this strategy will have significant implications for the preparation of nanogaps and enhanced spectroscopy.